The frontiers of public law - Public Law Conference 2018 : Melbourne, Vic.); Varuhas, Jason; Stark, Shona Wilson (Chicago, Illinois : Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This major collection contains selected papers from the third Public Law Conference, an international conference hosted by the University of Melbourne in July 2018. The collection includes contributions by leading academics and senior judges from across the common law world, including Australia, Canada, New Zealand, the United Kingdom and the United States. The collection explores the frontiers of public law, examining the intersection of public law with other signficant fields, and considering the possibilities for legal thought and legal development at public law's edges. The essays provide striking insights into public law, and its place within the wider legal landscape. The collection addresses four principal frontiers of public law - public law and international law; public law and indigenous law, rights and culture; public law and other domestic fields including private law and criminal law; and public law and public administration. In common with the two previous books in the Public Law Conference series, this collection provides invaluable insights at the cutting-edge of public law, and is a must-have for those working in the field"--
1. Introduction: The Frontiers of Public Law Jason NE Varuhas and Shona Wilson Stark -- PART 1 PUBLIC LAW AND INTERNATIONAL LAW 2. Global Constitutionalism: Myth and Reality Cheryl Saunders 3. Frontiers of Global Administrative Law in the 2020s Benedict Kingsbury 4. National Security Policy-making in the Shadow of International Law: The Case of the PPG Laura A Dickinson 5. Public Law in the UK after Brexit Jack Beatson and Emma Foubister -- PART 2 PUBLIC LAW AND INDIGENOUS PEOPLES 6. Indigenous Rights, Judges and Judicial Review in New Zealand Matthew SR Palmer 7. Coming to Terms with Communal, Land-related Decision-making by Aboriginal and/or Torres Strait Islander Peoples in a Public Law Context Debbie Mortimer 8. Representing Jurisdiction: Decolonising Administrative Law in a Multijural State Mary Liston 9. From the Heart: The Indigenous Challenge to Australian Public Law Kirsty Gover 10. Public Law, Legitimacy and Indigenous Aspirations Harry Hobbs 11. Places as Persons: Creating a New Framework for Maori-Crown Relations Andrew Geddis and Jacinta Ruru -- PART 3 PUBLIC LAW, CRIMINAL LAW AND PRIVATE LAW 12. Changing Boundaries: Crime, Punishment and Public Law David Feldman 13. Discretionary Power and Consistency: Is the Sentencing Discretion Different? Chris Maxwell 14. Public and Private Law: A Redundant Divide Carol Harlow 15. The 'Contracting State' and the Public/Private Divide ACL Davies 16. Public and Private Boundaries of Administrative Law Margaret Allars -- PART 4 PUBLIC LAW AND PUBLIC ADMINISTRATION 17. The Nature and Bounds of Executive Power: Keeping Pace with Change KM Hayne 18. Peering into the Black Box of Executive Power: Cabinet Manuals, Secrecy and the Identification of Convention Anne Twomey 19. Fomenting Authoritarianism Th rough Rules About Rulemaking Kathryn E Kovacs 20. Non-fettering, Legitimate Expectations and Consistency of Policy: Separate Compartments or Single Principle? Shona Wilson Stark 21. The In-between Space of Administrative Justice: Reconciling Norms at the Front Lines of Social Assistance Agencies Jennifer Raso 22. A 'Culture of Justification'? Police Interpretation and Application of the Human Rights Act 1998 Richard Martin.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Public law -- Congresses; Constitutional & administrative law; Electronic books